2022
DOI: 10.1002/jbm.a.37395
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular development in the rat arteriovenous loop model in vivo—A step by step intravital microscopy analysis

Abstract: The arteriovenous (AV) loop model is a key technique to solve one of the major problems of tissue engineering-providing adequate vascular support for a tissue construct of significant size. However, the molecular and cellular mechanisms of vascularization and factors influencing the generation of new tissue in the AV loop are still poorly understood. We previously established a novel intravital microscopy approach to study these events. In this study, we implanted our observation chamber filled with two types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 68 publications
1
8
0
1
Order By: Relevance
“…[19], к тому же в петле с применением фибрина образовались тромбы, что R. Vaghela и соавт. [30] связали с резорбцией фибринового скаффолда.…”
Section: артериовенозные петлиunclassified
“…[19], к тому же в петле с применением фибрина образовались тромбы, что R. Vaghela и соавт. [30] связали с резорбцией фибринового скаффолда.…”
Section: артериовенозные петлиunclassified
“…Neovessel outgrowth from the AV loop was analyzed as described previously [18,19]. Briefly, overlaid vessel network sketches for each High-Power Field (HPF) were prepared using the GNU Image Manipulation Program (GIMP).…”
Section: Microcirculatory Analysismentioning
confidence: 99%
“…This manuscript summarizes our efforts to establish IVM in the AV loop and evaluate its value for assessing vascular development in the AV loop. We have developed several different chamber designs [18,19]. Chamber design A allows repeated short-term (direct) imaging of the initial dynamic event following AV loop surgery, while chamber design B enables periodic longitudinal assessment of the vascularization and de novo tissue generation.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas predominantly clinical studies claim a safe use of lipotransfer [ 13 , 14 , 15 , 16 , 17 , 18 ], pre-clinical studies suggested an ADSC-induced promotion of breast cancer growth and tumor angiogenesis [ 9 , 19 , 20 , 21 , 22 ]. Among other factors, the role of vascularization in any recipient tissue for cell ingrowth or proliferation is certainly relevant [ 23 , 24 , 25 ]. Further, previous studies showed that ADSC can also influence healthy breast tissue and induce an epithelial-to-mesenchymal transition in mammary epithelial cells [ 26 ].…”
Section: Introductionmentioning
confidence: 99%